Effects of Lactation Feeder Design on Sow Bodyweight, Litter Performance, and Feeder Cleaning Criteria - Rafe Q. Royall; Karley R. Stephens; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Jordan T. Gebhardt; Robert D. Goodband; Kyle F. Coble (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 557 mixed parity sows (PIC 1050) were used to evaluate the effect of lactation feeder design on sow farrowing and litter growth performance during summer conditions. The experiment was conducted at a commercial sow farm located in northwest Texas with two sequential farrowing groups with approximately 279 sows per group. On d 112 to 114 of gestation, sows were moved to the farrowing house and randomly allotted to 1 of 3 feeder types based on parity and caliper score. Each of the three feeder types were equipped with the SowMax ad-lib sow feed hopper (Hog Slat). Feeder types consisted of: 1) a dry lactation feeder with a nipple drinker located next to the feeder; 2) a wet/dry lactation feeder with a divider to separate feed and water; or 3) the wet/dry lactation feeder without a divider. The three feeder types were placed in groups of three continuous stalls with the same sequence from the front to the end of all rooms to balance environmental effects. Sows were weighed before entering the farrowing house and at weaning. Sows were provided approximately 4 lb per day of a common lactation diet pre-farrowing. After farrowing, sows were provided ad libitum access to lactation feed. The weaning age averaged 20.9 d. There was no evidence of difference (P > 0.10) in sow weight or caliper score at entry, weaning, or overall BW change. Additionally, there was no evidence of difference (P > 0.10) in total litter or piglet birth BW, total pigs born, or percentage of pigs born alive. However, sows fed with the dry lactation feeder had decreased (P < 0.001) total daily feed disappearance, and average daily feed disappearance compared to sows fed with either wet/dry feeder. There was no evidence of difference (P > 0.10) for litter or pig weaning weight, or litter average daily gain. As a result, litter feed efficiency was improved (P = 0.027) in sows fed with the dry feeder compared to either wet/dry feeder. Sows fed with the dry feeder had decreased (P ≤ 0.006) total lactation feed cost and feed cost per piglet weaned compared to either wet/dry feeder. For feeder cleaning criteria, dry feeders had increased (P = 0.001) washing time and washing cost compared to either wet/dry feeder. In summary, using the dry feeder design reduced feed disappearance with no effects on sow and litter performance compared to either wet/dry feeder, thus improving litter feed efficiency and reducing feed cost per sow and litter presumably through less feed wastage.
Keywords: feed intake; lactation feeder; litter performance; sow; wet-dry feeder